2009
DOI: 10.1128/aac.01297-08
|View full text |Cite
|
Sign up to set email alerts
|

High Rate of Reduced Susceptibility to Ciprofloxacin and Ceftriaxone among Nontyphoid Salmonella Clinical Isolates in Asia

Abstract: This multinational study from Asia revealed that reduced susceptibility to ciprofloxacin (MIC, 0.125 to 1 g/ml) in nontyphoid Salmonella isolates was common in Taiwan (48.1%) and Thailand (46.2%) and in S. enterica serotype Choleraesuis (68.8%) and S. Virchow (75.0%) from all countries. Reduced susceptibility to ceftriaxone (MIC, 2 to 8 g/ml) remained uncommon in Asia, except in Taiwan (38.0%) or in S. Typhimurium (25.0%) from all countries.Nontyphoid Salmonella bacteria, with more than 2,500 serotypes, usuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
75
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 12 publications
8
75
3
2
Order By: Relevance
“…Antimicrobial resistance in Salmonella serotypes has been a global problem, with rates increasing from between 20% and 30% in the early 1990s to as high as 70% in some countries at the turn of the century [43,44]. The results of antimicrobial resistance tests of 111 Salmonella isolates to 16 antimicrobials are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial resistance in Salmonella serotypes has been a global problem, with rates increasing from between 20% and 30% in the early 1990s to as high as 70% in some countries at the turn of the century [43,44]. The results of antimicrobial resistance tests of 111 Salmonella isolates to 16 antimicrobials are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…In Asia, S. Enteritidis is also the most common in Hong Kong, Singapore, and Korea, whereas Salmonella serotypes Typhimurium, Weltevreden, and Stanley are the most prevalent in Taiwan, the Philippines, and Thailand (20). In Korea, serogroup D has been the most common among Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Taiwan (7) showed that between January 1999 and December 2002, only 1.02z of nontyphoidal Salmonella isolates were resistant to ceftriaxone. On the other hand, a multinational study (10) involving randomly collected non-typhoid isolates during 2003 to 2005 from 7 Asian countries (not including Malaysia) showed that reduced susceptibility to ceftriaxone (defined in that study as an MIC of 2-8 mg/ml) was uncommon in Asian countries, except Taiwan (38z), and in S. Typhimurium (25z) in all countries. It also reported a ceftriaxone resistance rate of 3.0z, compared with 10.8z in Taiwan (10).…”
mentioning
confidence: 93%
“…On the other hand, a multinational study (10) involving randomly collected non-typhoid isolates during 2003 to 2005 from 7 Asian countries (not including Malaysia) showed that reduced susceptibility to ceftriaxone (defined in that study as an MIC of 2-8 mg/ml) was uncommon in Asian countries, except Taiwan (38z), and in S. Typhimurium (25z) in all countries. It also reported a ceftriaxone resistance rate of 3.0z, compared with 10.8z in Taiwan (10). When comparing ceftriaxone resistance rates, the criteria used for interpretation as``resistant'' should be noted because the CLSI published revised ceftriaxone breakpoints in 2010 (14).…”
mentioning
confidence: 93%
See 1 more Smart Citation